Assessment and forecasting of the russian regions attractiveness as a factor of Interregional migration - R. V. Fattakhov; M. M. Nizamutdinov; A. R. Atnabaev; M. I. Akhmetzyanova (Управленческие науки)
Nowadays, one of the most important tasks of the state in the framework of ensuring sustainable socio-economic and demographic development of the country is the regulation of migration processes. The changes observed in a complex political situation, including the impact of sanctions and pandemics, have affected on the priorities transformation of the population when choosing a potential place of residence. In this regard, it is important and timely to identify trends and factors of population migration, as well as to assess the level of migration activity using modern economic and mathematical methods of analysis. These issues are most relevant for those regions where there is a migration outﬂow of the population. In order to identify the factors inﬂuencing a human behavior when making a decision to change their place of residence, a component analysis was conducted on 22 indicators of socio-economic development of 67 subjects of Russia. This process identifed fve main components. The obtained results formed the basis for assessing the level of attractiveness of the territories and further cluster analysis of the regions. This caused to the formation of four clusters, including the subjects of the Russian Federation with a similar level of socio-economic development. Combining the results of the multi-factor assessment made it possible to determine the complex level of socio-economic development for each region. At the next stage of the study, the identified relationships between the socio-economic development of the regions and the migration level were formalized using the methods of regression analysis. The obtained simulation results let the authors develop a forecast of the migration processes dynamics, taking into account the implementation of the inertial and optimistic scenarios for the development of the socioeconomic situation.